Impact of TP53 mutations in Triple Negative Breast Cancer - Zahi I. Mitri; Nour Abuhadra; Shaun M. Goodyear; Evthokia A. Hobbs; Andy Kaempf; Alastair M. Thompson; Stacy L. Moulder (npj Precision Oncology, 2022)
Abstract Identifying triple negative breast cancer (TNBC) patients expected to have poor outcomes provides an opportunity to enhance clinical management. We applied an Evolutionary Action Score to functionally characterize TP53 mutations (EAp53) in 96 TNBC patients and observed that EAp53 stratification may identify TP53 mutations associated with worse outcomes. These findings merit further exploration in larger TNBC cohorts and in patients treated with neoadjuvant chemotherapy regimens.